RELATIONS OF MINOR CHILDREN WITH PARENTS WHO ARE RESIDENTS IN MENTAL HEALTH CARE INSTITUTIONS - Pūras, Dainius; Šumskienė, Eglė (Socialinė teorija, empirija, politika ir praktika, 2009)
This research is one of the components of the project funded by European Commission "Child and Adolescent Mental Health in Enlarged European Union: Development of Effective Policies and Practices" (CAMHEE). Survey of the situation that occur in the families in which parents are placed into psychiatric residential homes due to mental illness, showed that development and implementation of effective parenting programs (as well as other community-based services for families at risk) might become an effective alternative to currently prevailing stigmatizing and paternalistic approach, including the concept of "bad" (incompetent) parents and their institutionalization. Based on the review and analysis of the situations in residential psychiatric care homes, one could observe that relations of the family members with residents of care homes and dynamics of these relations are greatly influenced by specifics of Lithuanian mental health and social care systems, historically developed stereotypes, public attitudes to mentally ill persons and information which is communicated to general public. It should be noted that the tradition dating back to Soviet-era ideology - that mentally ill persons need to be separated from family, community and society, is still strong.